Perancangan Sampul Buku Ilustrasi Pinjaman Online “Pinjol: Harapan atau Beban? - Shelvy Awailul Ramadhani; Restu Ismoyo Aji; Diana Aqidatun Nisa (Jurnal Riset Rumpun Seni, Desain dan Media, 2025)
The existence of online loan services in today's technological developments makes it easier for anyone who needs funds quickly because all processes can be done without face-to-face meetings. However, the conveniences offered are not without risks, especially for someone with low financial literacy. Lack of financial literacy in the use of online loan services often causes victims so that educational media is needed to help reduce this problem. Illustrated books were then chosen as one of the media for packaging information about online loans. The cover is the part of a book that is first seen visually, this aims to attract the attention of the target audience so that this study focuses on designing book covers. The data collection techniques used in this study are primary and secondary data collection techniques. Then analyzed using a mixed descriptive analysis technique. From the results of the analysis, the key word "Careful in Making Financial Decisions" was obtained, these keywords produce a cover design that is in accordance with the target audience.